Strategy For Strengthening The Akhlakul Karimah In The Lecturing Communication Process (Analysis of the Hijab Lecturer Steps in the Communication Department FISIP UNIB as Agents of Change in Minimizing the Bad Impact of Development of Era Communication Information Technology 4.0) - Lisa Adhrianti (AIUA Journal of Islamic Education, 2019)
The development of communication and information technology entering the4.0 era has had a positive and negative impact on the younger generation, especially among students who can later be called the millennial generation. Millennials that have a lot of contact with sophisticated technology machines will be able to give birth to a capable and skilled generation in many areas of life as well as able to erode the moral moral values due to the impact of unlimited virtual communication and tend to be value-free. Islam highly upholds the values of akhlakul karimah with adab-adab which have been regulated in the Quran and the Sunnah of the Prophet Muhammad that can be disseminated through polite communication full of gentleness by a lecturer who can act as an agent of change in society. The results of the study show that there are 5 (five) strategic steps that can be taken by a lecturer as agents of change as an effort to strengthen moral values, namely by building awareness, exchanging information, identifying problems, encouraging intentions to change, and transforming intentions into real action.